2010
DOI: 10.1002/ccd.22465
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus aspiration in primary percutaneous coronary intervention in high‐risk patients with ST‐elevation myocardial infarction: A real‐world registry

Abstract: In real-world all-comer STEMI patients with occluded infarct-related artery, thrombus aspiration prior to PCI improves coronary flow, myocardial perfusion, and long-term clinical outcome as compared with PCI in the absence of thrombus aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 31 publications
3
30
2
Order By: Relevance
“…The randomized clinical trial (RCT) TAPAS, in particular, showed that manual thrombus aspiration (TA) improved myocardial reperfusion and reduced mortality in STEMI patients at 1-year follow-up [5,6] . These results, confirmed by other studies [7][8][9][10] , including a meta-analysis [11] of 11321 patients from 20 RCT showing lower rates of late mortality, reinfarction and stent thrombosis in patients underwent manual TA compared with conventional primary PCI, led to a recommendation class Ⅱa for manual TA in patients undergoing primary PCI for STEMI [12] . Nevertheless, the use of the thrombectomy devices is still controversial and not routine in STEMI patients, especially because some studies have shown no impact on clinical outcome [13][14][15][16][17][18][19][20] , such as the TASTE trial [21] .…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…The randomized clinical trial (RCT) TAPAS, in particular, showed that manual thrombus aspiration (TA) improved myocardial reperfusion and reduced mortality in STEMI patients at 1-year follow-up [5,6] . These results, confirmed by other studies [7][8][9][10] , including a meta-analysis [11] of 11321 patients from 20 RCT showing lower rates of late mortality, reinfarction and stent thrombosis in patients underwent manual TA compared with conventional primary PCI, led to a recommendation class Ⅱa for manual TA in patients undergoing primary PCI for STEMI [12] . Nevertheless, the use of the thrombectomy devices is still controversial and not routine in STEMI patients, especially because some studies have shown no impact on clinical outcome [13][14][15][16][17][18][19][20] , such as the TASTE trial [21] .…”
Section: Introductionsupporting
confidence: 72%
“…Unlike other studies with strict inclusion criteria [6,10] , this registry demonstrated no impact of TA on both short and long-term outcomes. In the TAPAS trial [5,6] , only patients with primary PCI were included; in another real-world registry [10] , only patients with primary PCI indication and TIMI flow 0-1 were included.…”
Section: Clinical Outcomes Of Ta In Real-worldcontrasting
confidence: 57%
See 3 more Smart Citations